COVID-19 vaccine hesitancy: A narrative review of four South Asian countries - Ennab, Farah; Qasba, Rakhtan K.; Uday, Utkarsha; Priya, Priya; Qamar, Khulud; Nawaz, Faisal A.; Islam, Zarmina; Zary, Nabil (Frontiers in Public Health, 2022)
Objectives: Vaccine hesitancy remains a global issue, especially within poverty-stricken countries where there’s an interplay of financial and non-financial barriers. This narrative review aims to understand attitudes and behaviors towards COVID-19 vaccination in four South Asian countries and make context-specific recommendations to vaccine program drivers and decision-makers. Methods: A search was conducted using PubMed and Science Direct, and CINHAL from January 2020 up to May 2022 restricted to the English language for terms: “Afghanistan" OR "Pakistan" OR "India" OR "Bangladesh" in combination with "COVID-19 vaccine" and other related terms. All articles were initially included, and those with relevance were included in the synthesis of this paper. Results: A narrative review was performed for this study. Our narrative review included a total of eighteen studies with a sample size (n = 223 to 5237) averaging about 1325 participants per study conducted. The studies included revealed public hesitancy to receive the COVID-19 vaccine ranging from 6.3% to 56.2% with an average of 31.63% across all eighteen studies. Several reasons were linked to this observation in these four South Asian countries, and the predominant ones included: Insufficient information provided to the general public about the side effects of the vaccines, concerns regarding vaccine safety, and skepticism of vaccine efficacy. Conclusion: Vaccine hesitancy is a global problem within the context of COVID-19, and issues regarding equity, misinformation, and poverty in South Asian countries makes it difficult to meet goals for herd immunity. Policymakers and governments should aim toward financial and non-financial incentives to drive the public towards vaccination.